Residence of an entity for tax purposes – South Africa: a review of the concept ‘place of effective management - Majachani, Alex Farai (Centre for Law and Society, 2026)
The residence article in the OECD Model Tax Convention provides a `tie-breaker' rule for determining residence where an entity is resident in two different countries in order to avert double taxation. The residence of such a “dual resident” entity is allocated to the country in which its “place of effective management” is situated. One has to determine the location of an entity's PoEM in order to allocate taxing rights to one of the States so as to avert double taxation. According to the OECD, the PoEM is one where the key management and commercial decisions of an entity's business are made. This paper analyses the meaning and effectiveness of the concept ‘PoEM' as a tie-breaker rule. It is pointed out that the concept is under serious subversion by means of; inter alia, the exponential growth in e-commerce and the evolution of the communications technology. These developments have seen changes in the way business is run, including the conduct of board meetings. It is further highlighted that the concept suffers a lack of international agreement on its meaning and application. This article thus highlights these problems, and suggests recommendations to bolster the usefulness of the tie-breaker rule from a South African perspective.